PENERAPAN BUBUT MANUAL BERBASIS SOLIDWORKS PADA PEMBUATAN BAUT ADAPTOR FUEL PUMP DIESEL - Subhi, Ibnu; Koswara, Engkos (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
This practical work aims to apply manual turning methods based on design using SolidWorks software in the manufacturing process of a diesel fuel pump adaptor bolt. The stages include product design with SolidWorks, material selection of ST 37 steel, manual turning processes (facing, turning, drilling, chamfering, threading, and cutting), and product inspection. The results show that SolidWorks helps minimize dimensional errors during production, while ST 37 steel is suitable due to its ductility. The manual turning process successfully produced adaptor bolts with good precision according to specifications. In conclusion, the integration of CAD design with manual turning improves efficiency and product quality. It is recommended to enhance machining technology and consistently apply safety discipline during production.